2008
DOI: 10.1074/jbc.m702451200
|View full text |Cite
|
Sign up to set email alerts
|

Arc/Arg3.1 Translation Is Controlled by Convergent N-Methyl-D-aspartate and Gs-coupled Receptor Signaling Pathways

Abstract: Arc/Arg3.1 is an immediate early gene whose expression is necessary for the late-phase of long-term potentiation (LTP) and memory consolidation. Whereas pathways regulating Arc transcription have been extensively investigated, less is known about the role of post-transcriptional mechanisms in Arc expression. Fluorescence microscopy experiments in cultured hippocampal neurons revealed that Arc protein level was dramatically increased by activation of the cAMP-dependent protein kinase (PKA) pathway, which is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 58 publications
(62 reference statements)
4
66
0
Order By: Relevance
“…In cortical and hippocampal neurons, NMDA receptors are required for group I mGluR-dependent Arc transcription (14,20,42), whereas in striatal neurons mGluR5-mediated Arc induction is unaffected by NMDA antagonists (Fig. 4B).…”
Section: Discussionmentioning
confidence: 99%
“…In cortical and hippocampal neurons, NMDA receptors are required for group I mGluR-dependent Arc transcription (14,20,42), whereas in striatal neurons mGluR5-mediated Arc induction is unaffected by NMDA antagonists (Fig. 4B).…”
Section: Discussionmentioning
confidence: 99%
“…However, many neuromodulatory inputs to the hippocampus and cerebral cortex regulate protein synthesis-dependent plasticity. These afferents include dopaminergic inputs from the ventral tegmental area (Huang and Kandel, 1995, Kudoh et al, 2002, Tischmeyer et al, 2003, Huang et al, 2004, Smith et al, 2005, Nagai et al, 2007, Navakkode et al, 2007, Bloomer et al, 2008, Schicknick et al, 2008, Wang et al, 2010a), cholinergic inputs from the medial septal nucleus and the nucleus basalis magnocellularis (Frey et al, 2001, Massey et al, 2001, Frey et al, 2003, Bergado et al, 2007, McCoy and McMahon, 2007, Volk et al, 2007), and noradrenergic inputs from the locus ceoruleus (Straube et al, 2003, Walling and Harley, 2004, Gelinas and Nguyen, 2005, Gelinas et al, 2007, Bloomer et al, 2008). …”
Section: Local Protein Synthesis Throughout the Brainmentioning
confidence: 99%
“…For example, 5-HT agonist-induced increase in Arc mRNA was blocked by GYKI 52466 (Pei et al, 2004). Also, NMDA activation increased Arc mRNA, an effect prevented by NMDA receptor antagonists including MK 801 (Steward and Worley, 2001;Bloomer et al, 2008). Moreover, it has been reported that Group I (mGluR5) receptor activation increased Arc gene expression both in cultured neurones in vitro and brain tissue in vivo (Brackmann et al, 2004;Waung et al, 2008;Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…First, the selective AMPA receptor antagonist, GYKI 52466 (Nikam and Kornberg, 2001) was utilised given its role in defining 5-HT-glutamate interactions (Pei et al, 2004). Second, MK 801 and MPEP, selective antagonists at NMDA and mGluR5 receptors respectively, were used since evidence implicates a role for these co-excitatory receptors in the regulation of Arc expression (Steward and Worley, 2001;Brackmann et al, 2004;Lea and Faden, 2006;Bloomer et al, 2008;Bramham et al, 2010;Wang et al, 2009;Waung et al, 2008). Finally, the mGluR2/3 receptor antagonist, LY341495 was utilised in control experiments since activation of mGluR2/3 receptors inhibits neuronal activity and glutamate release, but does not recruit Arc expression (Cartmell and Schoepp, 2000;Bramham et al, 2010;Nicoletti et al, 2011;Linden et al, 2009 …”
Section: Introductionmentioning
confidence: 99%